REPARING ELIADEMY FOR E-LEARNING MEDIA IN ENGLISH LANGUAGE TEACHING - Yongki Perwonegoro; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2016)
Most of people like technology, especially for children even we life in needing technology the most era. Most of children think that study is the most boring thing. Demanded by the reason above, by using technology can enhance students’ interest to study. One of the appropriate technology is e-learning, using Eliademy. By using Eliademy, can also enhance students’ interest and ability in English. In using Eliademy as e-learning media only need personal computer and internet connection. Teacher and student have different account with different goal. Teacher prepares the course and the tasks that will be done by students. The students do the activity that is commanded by teacher. Students are demanded to read to complete the tasks. Students can also do discussion and seminar in some menus which are available in Eliademy.